Disulfide Bond in Pseudomonas aeruginosa Lipase Stabilizes the Structure but Is Not Required for Interaction with Its Foldase - Liebeton, Klaus (American Society for Microbiology, 2001)
Pseudomonas aeruginosa secretes a 29-kDa lipase which is dependent for folding on the presence of the lipase-specific foldase Lif. The lipase contains two cysteine residues which form an intramolecular disulfide bond. Variant lipases with either one or both cysteines replaced by serines showed severely reduced levels of extracellular lipase activity, indicating the importance of the disulfide bond for secretion of lipase through the outer membrane. Wild-type and variant lipase genes fused to the signal sequence of pectate lyase from Erwinia carotovora were expressed in Escherichia coli, denatured by treatment with urea, and subsequently refolded in vitro. Enzymatically active lipase was obtained irrespective of the presence or absence of the disulfide bond, suggesting that the disulfide bond is required neither for correct folding nor for the interaction with the lipase-specific foldase. However, cysteine-to-serine variants were more readily denatured by treatment at elevated temperatures and more susceptible to proteolytic degradation by cell lysates of P. aeruginosa. These results indicate a stabilizing function of the disulfide bond for the active conformation of lipase. This conclusion was supported by the finding that the disulfide bond function could partly be substituted by a salt bridge constructed by changing the two cysteine residues to arginine and aspartate, respectively.